Early changes in gene expression and inflammatory proteins in systemic juvenile idiopathic arthritis patients on canakinumab therapy. Issue 1 (December 2017) - Brachat, Arndt; Grom, Alexei; Wulffraat, Nico; Brunner, Hermine; Quartier, Pierre; Brik, Riva; McCann, Liza; Ozdogan, Huri; Rutkowska-Sak, Lidia; Schneider, Rayfel; Gerloni, Valeria; Harel, Liora; et al.
Abstract Background Canakinumab is a human anti-interleukin-1β (IL-1β) monoclonal antibody neutralizing IL-1β-mediated pathways. We sought to characterize the molecular response to canakinumab and evaluate potential markers of response using samples from two pivotal trials in systemic juvenile idiopathic arthritis (SJIA). Methods Gene expression was measured in patients with febrile SJIA and in matched healthy controls by Affymetrix DNA microarrays. Transcriptional response was assessed by gene expression changes from baseline to day 3 using adapted JIA American College of Rheumatology (aACR) response criteria (50 aACR JIA). Changes in pro-inflammatory cytokines IL-6 and IL-18 were assessed up to day 197. Results Microarray analysis identified 984 probe sets differentially expressed (≥2-fold difference;P < 0.05) in patients versus controls. Over 50% of patients with ≥50a ACR JIA were recognizable by baseline expression values. Analysis of gene expression profiles from patients achieving ≥50a ACR JIA response at day 15 identified 102 probe sets differentially expressed upon treatment (≥2-fold difference;P < 0.05) on day 3 versus baseline, including IL-1β, IL-1 receptors (IL1-R1 and IL1-R2), IL-1 receptor accessory protein (IL1-RAP), and IL-6. The strongest clinical response was observed in patients with higher baseline expression of dysregulated genes and a strong transcriptional response on day 3. IL-6 declined by day 3 (≥8-fold decline;P < 0.0001) and remained suppressed. IL-18 declined on day 57 (≥1.5-fold decline, P ≤ 0.002). Conclusions Treatment with canakinumab in SJIA patients resulted in downregulation of innate immune response genes and reductions in IL-6 and clinical symptoms. Additional research is needed to investigate potential differences in the disease mechanisms in patients with heterogeneous gene transcription profiles. Trial registration Clinicaltrials.gov:NCT00886769 (trial 1). Registered on 22 April 2009;NCT00889863 (trial 2). Registered on 21 April 2009.